Preoperative anxiety induces chronic postoperative pain by activating astrocytes in the anterior cingulate cortex region - Gu,Damin (2019)
SUMMARY OBJECTIVE The study aims to explore the relationship between preoperative anxiety and chronic postoperative pain. METHODS A total of forty rats were divided into four groups, control, single-prolonged stress alone, Hysterectomy alone, and SPS+ Hysterectomy. The paw withdrawal mechanical thresholds (PWMT) were examined. qRT-PCR and western blotting assay were performed to detect the GFAP expression in astrocytes isolated from the anterior cingulate cortex (ACC) region. In addition, the long-term potentiation (LTP) in ACC was examined. RESULTS Rats in the SPS group or the Hysterectomy alone group had no significant effect on chronic pain formation, but SPS can significantly induce chronic pain after surgery. Astrocytes were still active, and the LTP was significantly increased three days after modeling in the SPS+Hysterectomy group. CONCLUSIONS anxiety can induce chronic pain by activating astrocytes in the ACC region.